Analisis Kebijakan Kurikulum di Tsanawi Muassasah Assaqofatul Islamiyah Pondok Pombing di Pattani, Selatan Thailand - Abdulroman Mahir; Muhammad Hasbie Ashshiddiqi; Candra Wijaya (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2019)
The education curriculum applied by Muassasah Assaqofatul Islamiyah has so far not supported the development and understanding of Pattani's Malay children towards Islamic law. The main issues discussed were the Curriculum Policy Analysis in Tsanawi Muassasah Assaqofatul Islamiyah Pondok Pombing in Pattani (South Thailand). The purpose of this study was to find out in depth about the implementation and development of educational curriculums carried out in the Assaqofatul Islamiyah Muassasah. The method used in this study is qualitative descriptive. Data collection techniques using interviews were submitted to 18 respondents. In this processing technique there are 2 (two) activities, namely editing and tabulating. Data analysis techniques used in this study are qualitative descriptive techniques with data obtained in the form of information or descriptions of sentences (qualitative data) that are not related to numbers. The results showed that the educational objectives applied by Assaqofatul Islamiyah Islamic Education were not appropriate to the times, curriculum content was still lacking in forming students to achieve educational goals, the media did not fulfill learning, strategies or methods of education had not been used properly, there were still many shortcomings the process of education and learning evaluation is still not properly used. Based on an analysis of all of these factors (Education Curriculum), it can be concluded that the implementation of the education curriculum in the Assaqofatul Islamiyah (Pondok Pombing) Pattani (South Thailand) curriculum was not good enough.